The impact of plant growth-promoting bacteria on the functional and thermodynamic traits of Aptenia cordifolia and Carpobrotus edulis under recycled water irrigation in external green wall conditions - Mansoure Jozay; Hossein Zarei; Sarah Khorasaninejad; Taghi Miri (Agricultural Water Management)
Nature-based solutions (NBS), exemplified by external green walls, play a crucial role in bolstering the sustainability of cities by mitigating heat islands and moderating temperatures. Nevertheless, owing to the lavish consumption of urban water in green walls, the adoption of recycled water for irrigation within these infrastructures emerges as a widely employed strategy. We conducted an investigation on the accumulator ornamental species Aptenia cordifolia and Carpobrotus edulis, exploring the effects of treatments involving recycled water and the application of PGPR. This research consisted of two separate experiments, each focused on a different plant species. The experiments were structured as split-plot layout based on a randomized complete block design with three replications from March to December 2022 on an external green wall. The main factor was recycled waters with three levels (gray water, wastewater from the Kashfroud region of Mashhad, and urban water (control)). The sub-factor included different bacterial strains at four levels, composed of various bacterial combinations such as B1, B2, B3, and B0 as the control level without bacterial application. The results indicated that the highest number of flowers per individual plant (6.58) and in the unit (9.33), flower diameter (8.98 mm), leaf surface area (66.26 cm3), and fresh and dry biomass (322.40 g per plant and 35.93 g per plant, respectively) were recorded in A. cordifolia with Mix B3 and irrigation with wastewater. Meanwhile, in the Carpobrotus, the highest leaf surface area (70.31 cm3) was associated with Mix B3 and irrigation with gray water. The Carpobrotus, with Mix B1, had the highest fresh biomass (393.71 g per plant), and with Mix B3, it exhibited the highest dry biomass (35.93 g per plant) when irrigated with wastewater. According to the results in A. cordifolia and C. edulis, Mix B3 and irrigation with wastewater increased WUE by approximately 40 % in the spring and autumn seasons. It is noteworthy that during the summer season, WUE exceeded 50 % based on the growth index. The results of this study recommend the combination of the substrate with Mix B3 and irrigation with wastewater, along with using A. cordifolia instead of other unstable plants on the external green wall in dry and semi-dry climates.